The Influence of Brand Image and Product Quality on Customer Loyalty Through Customer Satisfaction in the Use of the BSI Mobile Application - Muhammad Krisna Eka Syahputra,; Ari Dwi Astono,; Anissa Fajri, (Economics and Business International Conference Proceeding, 2024)
This research was conducted at the University of Muhammadiyah Semarang which is located at Kel. Kedungmundu, Kec.Tembalang, Semarang City, Central Java. Sample Determination in this study uses Nonprobability Sampling Technique which uses Purposive Sampling technique, where sample selection is based on criteria that have been determined by the researcher. The population of this study is regular students of the Management Study Program batch 2020-2023, Faculty of Economics at the University of Muhammadiyah Semarang which totals 974 students. The research sample consisted of 91 respondents. Data analysis method using quantitative data with the help of SmartPLS 4.0 Software. The results showed that X1 to Y has a positive and significant influence because the value of the beta coefficient X1 to Y is 0.337, t-statistics is 3.617, then X2 to Y has a negative and insignificant influence. Because the value of the beta coefficient X2 to Y is -0.052 with a t-statistics value of -0.052, then the influence of purchasing decisions as a mediation variable